2020
DOI: 10.1139/cjz-2019-0089
|View full text |Cite
|
Sign up to set email alerts
|

Big and bad: how relative predator size and dietary information influence rusty crayfish (Faxonius rusticus) behavior and resource-use decisions

Abstract: Prey animals use the information that they extract from predator cues to assess risk. Animals can obtain information about the relative size of predators and their dietary constituents from odor cues that predators deposit in the environment. However, it is currently unknown how prey animals respond when presented with two or more pieces of information about a predator. Rusty crayfish (Faxonius rusticus (Girard, 1852)) were exposed to odors from predatory largemouth bass (Micropterus salmoides (Lacepède, 1802)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Hence, cladocerans seem to be capable of responding even to larvae of different Chaoborus species, and/or to larvae at different developmental stages [26,84]. The potential recognition of predator size by the prey is in concordance with a study on crayfish, showing that crayfish are able to respond differently to specific predator sizes [85], pointing towards a high complexity of defence-inducing cues (see below). Thus, it is reasonable to assume that such a mechanism for predator-size-specific responses also evolved in other species such as freshwater dwelling zooplankters.…”
Section: Behavioural Defencessupporting
confidence: 68%
“…Hence, cladocerans seem to be capable of responding even to larvae of different Chaoborus species, and/or to larvae at different developmental stages [26,84]. The potential recognition of predator size by the prey is in concordance with a study on crayfish, showing that crayfish are able to respond differently to specific predator sizes [85], pointing towards a high complexity of defence-inducing cues (see below). Thus, it is reasonable to assume that such a mechanism for predator-size-specific responses also evolved in other species such as freshwater dwelling zooplankters.…”
Section: Behavioural Defencessupporting
confidence: 68%
“…In all laboratory experiments, there is some degree of confinement effect for both predator and prey behaviour. Predation can be mediated by structural complexity (amongst other factors) for example by changing predator free space (Barrios‐O'Neill et al 2015), increasing shelter use leading to less active foraging (Wood & Moore, 2020), or act as a prey aggregator (Persson & Eklov, 1995). Therefore, we emphasize that these results are relative in the context of this experiment, although FR results have been shown to be predictive and meaningful in terms of ecological impact across many taxa (Cuthbert et al., 2019; Dick et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The first demonstrated that crayfish increased macrophyte consumption and showed altered macrophyte species preferences in the presence of predatory fish odors (Wood et al 2018). The other studies showed that crayfish could assess the threat posed by a predatory fish using dietary cues and size information extracted from the fish’s odor (Beattie and Moore 2018, Wood and Moore 2020). The current study demonstrates that individual crayfish assess threats posed by fish of different sizes relative to their own body size and alter their behavior accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The predator exposed crayfish also increased the time that they spent foraging and reduced the time they spent in shelter. In a second experiment, crayfish were exposed to odors from bass of different sizes that were fed four different diets consisting of fish food pellets and three types of crayfish (Wood and Moore 2020). The responses of crayfish to the relative predator size gradient were dependent upon the predator’s diet.…”
Section: Introductionmentioning
confidence: 99%